A Perceptual Illusion of Empty Space Can Create a Perceptual Illusion of Levitation. (December 2019) - Øhrn, Heidi; Svalebjørg, Mats; Andersen, Steffen; Ring, Anna Edit; Ekroll, Vebjørn
A recent analysis of magic tricks suggests the existence of a perceptual illusion where the space hidden behind an occluding object is experienced as empty in a strangely compelling way. Here, we show that this illusion of absence is not just a trivial consequence of the lack of retinal stimulation but rather the result of an active process of perceptual construction. The results of a simple experiment show that this perceptual illusion of absence can in turn trigger perceptual processes which generate an immediate perceptual impression of levitation via a percept–percept coupling. This suggests that magical illusions of levitation are partially driven by an immediate perceptual impression of floating in thin air. The perceptual mechanisms underlying the illusion of absence are hitherto unknown, but our results provide support for a potential explanation based on the generic view principle.